Cyclohexanone and Phenolic Acid Derivatives from Endophytic Fungus Diaporthe foeniculina - Lu, Xiuxiang; Zhang, Yanjiang; Zhang, Wenge; Wang, Huan; Zhang, Jun; Wang, Sasa; Tan, Haibo (Frontiers in Chemistry, 2021)
Chemical investigation of an endophytic fungus Diaporthe foeniculina SCBG-15, led to the isolation of eight new cyclohexanone derivatives, foeniculins A–H (1–8) and three new phenolic acid derivatives, foeniculins I–K (9–11). Their structures were extensively established on the basis of 1H and 13C NMR spectra together with COSY, HSQC, HMBC, and NOESY experiments. The absolute configurations were confirmed by quantum chemical ECD calculations and single-crystal X-ray diffractions. Moreover, the in vitro cytotoxic and antibacterial activities of isolated compounds 1–11 were also evaluated.